SQOR as a metabolic rheostat of H2S: structure, redox homeostasis, and disease therapy - Peng, Ming-Hui; Zhang, Kai-Lun; Ma, Zhong-Wu; Zhang, He-Wei; Guan, Shi-Wei; Yu, Hai-Bo (Frontiers in Cell and Developmental Biology, 2025)
Sulfide:quinone oxidoreductase (SQOR) is an inner-mitochondrial-membrane enzyme that couples hydrogen sulfide oxidation to the coenzyme Q pool, thereby linking sulfur metabolism with cellular bioenergetics and redox control. Recent structural and mechanistic advances—most notably the catalytic cysteine trisulfide—clarify how membrane context and substrate availability tune catalytic flux, yet debate persists over the physiological sulfur acceptor (glutathione versus sulfite) and how microenvironments route sulfide. SQOR also shapes ferroptosis: by using hydrogen selenide to reduce ubiquinone, it elevates ubiquinol and suppresses lipid peroxidation independently of glutathione peroxidase-4. We synthesize cross-system disease evidence—brain (hypoxia/ischemia, neuroinflammation), heart (divergent roles in acute ischemia–reperfusion versus chronic failure), kidney (mitochondrial dysfunction and cGAS–STING(cyclic GMP–AMP synthase–stimulator of interferon genes)–driven fibrosis), gastrointestinal tract (stage-specific effects in colorectal cancer and impaired detoxification in ulcerative colitis), bone/metabolic disorders, and the male reproductive system—highlighting SQOR’s bidirectional pathology when hydrogen sulfide is excessive or depleted. Viewing SQOR as a “metabolic rheostat” reconciles these paradoxes and underscores therapeutic opportunities: metabolic supplementation (e.g., coenzyme Q10), selective inhibition or activation, and context-matched modulation. We further propose companion diagnostics that quantify sulfur/selenium species and enzyme activity to enable patient stratification and de-risk clinical translation.